Aplikasi Well Logging untuk Penempatan Pipa Saringan Sumur Bor Air Tanah di Desa Banyu Irang Kecamatan Bati-Bati, Kalimantan Selatan - Hisna Baiti; Simon Sadok Siregar; Sri Cahyo Wahyono (Jurnal Fisika FLUX, 2016)
The water needs extremely increases along with the rate of population growth in Bati-Bati district year by year. Unfortunately, the clean water supply is limited. Factually, the clean water is really needed considering the role of it, which is essential for the life sustainability and industrial necessity. The water can be from the groundwater which can be obtained from aquifer. Therefore, this study aims at determining the aquifer layer to set the bore well filter pipe. To determine the aquifer layer is by arranging stones litology of bore wells based on bore cutting result which is correlated with the data result of Well Logging. Cutting bore result is obtained from the rock flakes lifting to the surface by being drilled. Furthermore, the data of well logging result is got by measuring. Well Logging uses Rescsalog product, which results in the reading of Log Gamma Ray, Resistivity and Log Spontaneous Potential. The result is the first well filter pipe position is set in 57-61, 66-98 and 115-125 m. Meanwhile, the second well is set in 43-51, 79-82, 99-102, 105-119 and 130-133 m.